A review of performance and symptom validity testing with pediatric populations. Issue 4 (1st October 2020) - Kirk, John W.; Baker, David A.; Kirk, Jennifer J.; MacAllister, William S.
Abstract: Growing recognition and concerns of non-credible performance in pediatric populations have led clinicians to investigate the utility of performance and symptom validity tests (PVT/SVTs) among children and adolescents. Yet current research has indicated that a minority of clinicians routinely utilize a free-standing PVT in pediatric neuropsychological evaluations. The current article investigates the rationale for using PVT/SVTs, and the impact that failure of such exams have on other neurocognitive tests. A review of common adult PVTs and their appropriateness for use with specific pediatric clinical populations is presented, as well as empirical evidence for evaluating embedded validity indicators. The limited literature on SVTs with youth is also reviewed and provides additional insight into symptom exaggeration. There are various reasons children would provide noncredible performance, many of which are different from adults. A review of how the clinician should handle this behavior in pediatric evaluations is provided and what patient populations may present with a higher base rate of failure. Finally, various approaches are offered on how to explain these results to children and their caregivers.